Fatores associados à ideação suicida e ao risco de suicídio em acadêmicos do curso de enfermagem de uma universidade pública do Norte do Brasil - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Objective: To investigate the factors associated with suicidal ideation and suicide risk in nursing students at the Federal University of Amapá. Methods: Descriptive cross sectional study. 98 Nursing students from the Federal University of Amapá (UNIFAP) participated, in which a questionnaire was applied with items related to sociodemographic characteristics, life habits and the university environment and Beck's Suicidal Ideation Scale (BSI). Results: The average age of students is 22.6 years, most of whom are female and, despite claiming to have suicidal thoughts, the BSI indicated suicidal ideation in 32.8% and suicide attempt in 16.4%. Final considerations: It is concluded that there is the presence of suicidal ideation, as well as the suicide attempt, making it essential to identify attitudes that may cause psychic suffering, opening possibilities for new discussions and possible solutions. In addition to bringing the protagonists of the academic environment closer to the prevention of this phenomenon and contributing to the promotion of mental health in the academic community.
Keywords: Suicídio; Enfermagem; Ideação Suicida; CNPQ::CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; ODS 3 – Saúde e bem-estar; ODS 4 – Educação de qualidade